Uma análise ecológica e evolutiva dos lagartos em um simulador para o jogo calangos - Izidoro, Venyton Nathan Leandro (2016)
The educational game Calangos is based on the ecological modeling of a real case of lizards that inhabit the Dunes of the Middle São Francisco River, in the state of Bahia - Brazil. The goal of the game is to enable students to interact with an environment that promotes a proper understanding of ecological and evolutionary processes. The game should serve as a tool to support the teaching and learning of ecology and evolution to high school students. For the Calangos Game to achieve this goal, central concepts of evolution and ecology should be properly incorporated in the game. Thus, the first scientific challenge of the project, in addition to the technological challenge of developing the game itself, is related to modeling the population dynamics and evolutionary biology in the context of Calangos. To investigate these aspects independently of the game, this dissertation proposes a simulator for Calangos, as well as a genetic-evolutionary model for the lizards. Furthermore, it performs a set of experiments that examine the ecology and evolution of the lizards in the proposed simulated environment. More specifically, four experimental scenarios and three difficulty levels for each environmental scenario are proposed to carefully analyze the dynamics of populations and the influence of the evolution on the fertility and longevity of lizards populations located within the simulated environment. The results clearly show that in a balanced environment without predators it is possible to observe a dynamic equilibrium of populations in a typical Lotka-Volterra model of population dynamics. On the other hand, it is also observed that in the most hostile environments containing large numbers of predators, the capability of evolution allows the lizard species to survive in the environment, which does not occur if the lizards evolution is disabled during the simulations. In the context of the Calangos game, the results presented here serve as the initial proof of concept necessary for the modeling of the lizards to be incorporated in the game.